Kematangan Fisik dan Mental dalam Perkawinan - Muhammad Agus Kurniawan (Postgraduate State Islamic Institute (IAIN) Metro, 2014)
To create the feel secure in the marriage, the adult candidate is needed, physically and mentally. However, the preachers have different views about the meaning of manhood. Islamic law indicates that couples getting married have to mature physically and mentally. Thus, under the laws of our government is 1/1974, Article 7, paragraph (1), it is said that marriage is allowed only if the groom was 19 and the bride was 16. In Islam, marriage position has an important role in the survival of a family. Besides in a hadith history explained, marriage is one way for someone to reach heaven. In Indonesia, the law of marriage is also arranged. Starting from the terms of the age, the condition of validity to be a guardian. If one of the pillars is not completed, then in the view of Islam held to be invalid or void.